Congenital RYR1-Associated Myopathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators from the Children's Hospital of Philadelphia, NINDS, and other centers in the US and France, report a series of 11 patients with severe neonatal RYR1-associated myopathy confirmed by genetic testing.